2014
DOI: 10.1210/jc.2013-4381
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain Reveals Dramatic Increases in Skeletal Muscle Extracellular Matrix Remodeling

Abstract: We propose that skeletal muscle extracellular matrix remodeling is another feature of the pathogenic milieu associated with energy excess and obesity, which, if disrupted, may contribute to the development of metabolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 26 publications
1
66
2
Order By: Relevance
“…Consistent with a previous study [18] , there were no changes in the expression of macrophage markers or circulating MCP-1, although we noted that the degree of weight gain was associated with an increase in MCP-1. This data adds to the growing body of evidence that the inflammatory response may occur subsequent to insulin resistance in humans [18,[25][26][27] . Adiponectin exhibits that anti-diabetic, anti-atherogenic, anti-inflammatory and cardioprotective functions is reduced in obesity [28] , and increased in response to weight loss [29] .…”
Section: Discussionmentioning
confidence: 61%
“…Consistent with a previous study [18] , there were no changes in the expression of macrophage markers or circulating MCP-1, although we noted that the degree of weight gain was associated with an increase in MCP-1. This data adds to the growing body of evidence that the inflammatory response may occur subsequent to insulin resistance in humans [18,[25][26][27] . Adiponectin exhibits that anti-diabetic, anti-atherogenic, anti-inflammatory and cardioprotective functions is reduced in obesity [28] , and increased in response to weight loss [29] .…”
Section: Discussionmentioning
confidence: 61%
“…Alligier et al [85] observed increases in lipid metabolism genes at 14 days, followed by increases in ECM genes and genes related to adipogenesis and angiogenesis at 56 days, which was supported by histological examination. Similarly Tam et al [112] reported significant increases in adipose tissue expression in collagens I and II and TGFβ after 10% weight gain, although no changes were noted in expression of inflammatory genes in either study suggesting change in the ECM was independent of macrophage infiltration.…”
Section: Does Macrophage Infiltration Promote Healthy Adipose Tissue mentioning
confidence: 74%
“…Furthermore whereas there was no differential increase in fat mass among treatment groups, lean body mass was increased in the normal-and high-protein diet groups but not the low-protein diet group. This finding suggests that the body mass differences are likely not traditional healthy lean body mass (i.e., muscle and water) but instead are comprised of extracellular matrix and other structural proteins supporting adipose tissue expansion (32) and even possibly liver proteins. Our results are similar to others.…”
Section: Discussionmentioning
confidence: 99%